Laparoscopic cervicopexy in uterine prolapse, a prospective study - Aliyar, Anu; Palakkan, Saphina; Vahab, Abdul; P., Mumtaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pelvic organ prolapse is a common condition and a major cause of gynecological surgery. The lifetime risk of having an operation for prolapse may be 11%. Uterine conserving surgeries using synthetic mesh, especially in younger age group can restore normal anatomy relieving their pelvic symptoms. To evaluate the safety, intra operative and postoperative complications and efficacy of the laparoscopic cervicopexy. Methods: This Prospective observational study was carried out on women aged below 45 years attending gynaecology outpatient department with uterine prolapse at MES Medical College, Perinthalmanna between January 1st and December 31st, 2015. 39 women underwent laparoscopic cervicopexy and follow up assessments was done among them at 2 weeks, 3 months and 6 months. Results: The mean operative time was 27.6 minutes and blood loss was 0.4 gm/dl. No intraoperative and postoperative complications occurred. Short duration of hospital stay with mean of 1.4 days. 7.7% patients and 5.5% had mersilene tape reaction at 3 months and 6 months. The POP Q score C was significantly away from hymen at 2 weeks,3 months and 6 months (+4.4 - -4.3). 7.7% and 2.6% had recurrence at 3 month and 6 months. 5.1% underwent vaginal hysterectomy to get relieved from symptom. Conclusion: Laparoscopic cervicopexy is an effective option for women with pelvic organ prolapse who desire uterine preservation.